Potent Natural Soluble Epoxide Hydrolase Inhibitors from Pentadiplandra brazzeana Baillon: Synthesis, Quantification, and Measurement of Biological Activities In Vitro and In Vivo - Kitamura, Seiya; Morisseau, Christophe; Inceoglu, Bora; Kamita, Shizuo G.; De Nicola, Gina R.; Nyegue, Maximilienne; Hammock, Bruce D. (PLOS ONE, 2015)
We describe here three urea-based soluble epoxide hydrolase (sEH) inhibitors from the root of the plant Pentadiplandra brazzeana. The concentration of these ureas in the root was quantified by LC-MS/MS, showing that 1, 3-bis (4-methoxybenzyl) urea (MMU) is the most abundant (42.3 μg/g dry root weight). All of the ureas were chemically synthesized, and their inhibitory activity toward recombinant human and recombinant rat sEH was measured. The most potent compound, MMU, showed an IC50 of 92 nM via fluorescent assay and a Ki of 54 nM via radioactivity-based assay on human sEH. MMU effectively reduced inflammatory pain in a rat nociceptive pain assay. These compounds are among the most potent sEH inhibitors derived from natural sources. Moreover, inhibition of sEH by these compounds may mechanistically explain some of the therapeutic effects of P. brazzeana.